Computer Knowledge Improvement Training Students Dropping Out of School in Buluh Apo Village: Pelatihan Peningkatan Pengetahuan Komputer Siswa Putus Sekolah Pada Desa Buluh Apo - Teuku Radillah; Leonard Tambunan; Budy Satria; Irman Efendi; Chalida Hanum (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Buluh Apo village is a village that is located far out of town Duri, however, the Head of Buluh Apo Village has a vision to develop his village through the implementation of computer technology science, so that this village also has the nickname Net Village, because it has an internet network developed with the community. The purpose of this service is a collaborative program between the Apo Buluh village apparatus and the AMIK Mitra Gama campus to improve the quality of computer science in the current pandemic (COVID-19) conditions which require students to study more online (online) and for students dropping out of school. can Buluh Apo Village is a village located far on the outskirts of Duri city, however, the Head of Buluh Apo Village has a vision to develop his village through the implementation of computer technology knowledge. The purpose of this service is a collaborative program between Buluh Apo village officials and the Mitra Gama Institute of Technology campus to improve the quality of computer science for dropout students to be able to take advantage of this training to provide skills in the computer field so that they can become entrepreneurs in the field of informatics so that they can still participate in advance Buluh Apo village. The training participants totalled 30 dropout students with the achievement of target material including an introduction to computers and Microsoft Office. In this computer introduction training the results of student participation were achieved with an attendance of85%, an increase in student knowledge reaching 75%, students' skills in using Ms Office reached 78%, the ability to use the internet increased by 87%, and the understanding of entrepreneurs in the field of informatics by 84%, and the development of hardware and multimedia reached 77%